(untitled) (Al-Academy, 2025)
In view of the technological development in recent periods of time, there have been needs that have become an urgent necessity for advanced society. The need for technology has entered into many fields, especially the digital field and technologies that have created a world similar to our world. The graphic designer was able to present an idea inspired by dream, imagination, and unreality, adding to it formal effects that he created. By employing it through the beauty of form, content, and consistency so that it serves the advertising design message, as he placed interconnected additions in terms of the interior and exterior, which makes the surrealist design structure innovative, creative, and creative, since the advertisement is the link between the designer and the recipient. 1- The use of the surreal form appeared in all models that bear the character of exotic art, and through the exotic form the designer was able to move away from the familiar and the traditional. 2- The innovative form in the posters is surreal, according to the designer’s imaginative and unusual idea. The surreal design form may be strange, and this calls for drawing the recipient’s attention to the surreal design content.